Effects of Rapid Water-Level Fluctuations on the Stability of an Unsaturated Reservoir Bank Slope - Jin-Zhu Mao; Jia Guo; Yong Fu; Wei-Peng Zhang; Ya-Nan Ding (Advances in Civil Engineering)
The instability of reservoir slope is likely to cause some severe natural hazards such as surge and barrier lake. In this study, the changes in seepage field and the distribution of the unsaturated zone of a reservoir bank slope subjected to rapid water-level fluctuations are investigated using the finite element method. The stability analysis of a reservoir slope under water-level fluctuation with a rate of 2 m/day is performed. The stability analysis is based on the theory of unsaturated soil mechanics and saturated-unsaturated seepage and accounts for the hydromechanical coupling effect. The changes in shear stress and strain as well as pore water pressure due to rapid water-level fluctuations are explicitly examined. Furthermore, the stability factor of safety, the underlying failure mechanism, and relevant influence factors are discussed. Based on the finite element analysis, it is found that the rapid loss of matrix suction would give rise to the surface landslide near the slope toe.